Identifikasi Proses Bisnis pada Pengelolaan Hotel - Firhah, Fina Maslahatul; Salsabila, Zauda Salma; Yaqin, Muhammad Ainul (Jurnal Teknik Informatika dan Elektro, 2025)
The hospitality industry faces challenges in improving operational efficiency and customer satisfaction amid increasingly fierce competition. One approach that can be used is Porter's value chain analysis, which helps identify and optimize each activity in the business process to increase the value provided to customers. This study aims to analyze the application of the Porter Value Chain method in optimizing hotel business processes, focusing on identifying the main and supporting activities that contribute to operational efficiency. The method used in this research is a qualitative approach with a case study design, which involves in-depth interviews, observation, and document analysis related to hotel operations. The results showed that the application of Porter's Value Chain helped the hotel in identifying areas for improvement, such as the booking process, facility management, and additional services. In addition, this study also reveals that by optimizing technology, hotel business processes can be more efficient and responsive to customer needs. This research suggests that hotels should focus more on managing technology and human resources to improve service quality and lower operational costs.